Using primary tumor volumetry to predict treatment outcome for patients with oropharyngeal cancer who were treated with definitive chemoradiotherapy. Issue 2 (7th June 2017) - Lee, Yun Hee; Song, Jin Ho; Choi, Hoon‐Sik; Jeong, Hojin; Kang, Ki Mun; Kang, Jung Hun; Woo, Seung Hoon; Park, Jung Je; Kim, Jin Pyeong; Jeong, Bae Kwon
Abstract: Aim: This study aimed to determine predictive values for volumetric measures in patients with oropharyngeal cancer who received definitive chemoradiotherapy (CCRT). Methods: Contrast‐enhanced computed tomography (CT) scans were obtained before radiotherapy (RT) (I), after delivering a median RT of 50.6 Gy (R) and three months after RT (F). Primary site gross tumor volumes (GTV) were assessed using these scans (GTVI, GTVR and GTVF ). The percentage volume change between GTVI and GTVR (GTV change) was calculated. Volumetric analyses of primary site local control (LC) and progression‐free survival (PFS) were performed. Results: In total, 35 patients were evaluated, with a median 31 months of follow‐up. The 2‐year LC rates (LCRs) were 95.0% for patients with GTVI <23 cc, and 42.9% for those with GTVI ≥23 cc ( P = 0.001); the 2‐year PFS rates were 85.9% and 21.9% ( P = 0.002), respectively. Using GTVR classifications <11 cc or ≥11 cc, log‐rank tests demonstrated differences in 2‐year LCR (95.2% vs 33.3%, P < 0.001) and 2‐year PFS (86.5% vs 0%, P < 0.001). There was no local progression in patients with GTV change ≥75%, and GTV change predicted poor PFS ( P = 0.026). On multivariate analysis, GTVR ≥11 cc was a significant predictor of poor LCR (hazard ratio [HR] = 26, P = 0.009) and PFS (HR = 8.33, P = 0.046). Conclusion: For patients with oropharyngeal cancer treated with definitive CCRT, GTVI, GTVR and GTV changes predicted LC and PFS; GTVR was the most significant predictor of LC and PFS. RT intensification should be considered for patients with larger remaining tumors after CCRT.